Were the Keynesians loyal followers of Keynes? (2007)
Tribal warfare is not the most attractive feature of contemporary economics, even if it is much the most exciting. But the vigour of debate occasionally makes it less careful and precise. Distinguished economists become misled by their own slogans and tend to assert glibly what they know should be argued cautiously. One particular vice is the habit of attaching a brand name to a school of thought, not with the intention of designating a common theme, but with that of heightening rhetorical impact. It is right to be suspicious of this tendency because it conveys a possibly spurious impression of unanimity, of a confederation of intellects, which can persuade non-participants in the debate by sheer force of numbers. But there can be a still more serious reason for distrust. When the confederation becomes known by a special name there is a danger that the name can give a distorted idea of the quality of its intellectual weaponry. The danger is greatest when the name used is that of a much revered warrior, now dead, who achieved a number of famous victories in his lifetime.